Defining the Key Competencies in Radiation Protection for Endovascular Procedures: A Multispecialty Delphi Consensus Study. (February 2018) - Doyen, Bart; Maurel, Blandine; Cole, Jonathan; Maertens, Heidi; Mastracci, Tara; Van Herzeele, Isabelle; ,
Abstract : Objectives: Radiation protection training courses currently focus on broad knowledge topics which may not always be relevant in daily practice. The goal of this study was to determine the key competencies in radiation protection that every endovascular team member should possess and apply routinely, through multispecialty clinical content expert consensus. Methods: Consensus was obtained through a two round modified Delphi methodology. The expert panel consisted of European vascular surgeons, interventional radiologists, and interventional cardiologists/angiologists experienced in endovascular procedures. An initial list of statements, covering knowledge skills, technical skills and attitudes was created, based on a literature search. Additional statements could be suggested by the experts in the first Delphi round. Each of the statements had to be rated on a 5- point Likert scale. A statement was considered to be a key competency when the internal consistency was greater than alpha = 0.80 and at least 80% of the experts agreed (rating 4/5) or strongly agreed (rating 5/5) with the statement. Questionnaires were emailed to panel members using the Surveymonkey service. Results: Forty-one of 65 (63.1%) invited experts agreed to participate in the study. The response rates were 36 out of 41 (87.8%): overall 38 out of 41(92.6%) in the first round and 36 out of 38 (94.7%) in the second round. The 71 primary statements were supplemented with nine items suggested by the panel. The results showed excellent consensus among responders (Cronbach's alpha = 0.937 first round; 0.958 s round). Experts achieved a consensus that 30 of 33 knowledge skills (90.9%), 23 of 27 technical skills (82.1%), and 15 of 20 attitudes (75.0%) should be considered as key competencies. Conclusions: A multispecialty European endovascular expert panel reached consensus about the key competencies in radiation protection. These results may serve to create practical and relevant radiation protection training courses in the future, enhancing radiation safety for both patients and the entire endovascular team.